El camino incierto de la gestión de los datos - García-García, Alicia; Peset, Fernanda (Anuario ThinkEPI, 2015)
Reseña del informe: Council on Library and Information ResourcesÂ (2013).Â Research data management: Principles, practices, and prospects. Washington, DC: CLIR.Â ISBN: 978 1 932326 47 5 Â http://www.clir.org/pubs/reports/pub160/pub160.pdf